Viabilidade econômica do cultivo da alface crespa em monocultura e em consórcio com pepino - da Silva, Gilson Silverio [UNESP]; Alves Rezende, Braulio Luciano; Cecilio Filho, Arthur Bernardes [UNESP]; Barros Junior, Aurelio Paes; Espagnoli Geraido Martins, Maria Inez [UNESP]; de Queiros Porto, Diego Resende [UNESP] (Universidade Federal de Lavras (UFLA), 2008)
The protected culture, among other advantages, made possible to diminish the seasoning in offers and to improve the quality of vegetables. However, one consists in technology of high cost, that it may be attenuated with the increase in the efficiency of the use of the protected area, proportionated for the intercropping. The experiment was carried out at greenhouse at UNESP, Jaboticabal-SP, in the period of August and November of 2005, with the aim of evaluating the operational cost (COT) and the profitability of the crisphead lettuce "Veronica" (Lactuca sativa L.) in monoculture and in intercropping with the Japanese cucumber "Hokushin" (Cucumis sativus L.), in protected environment. The main cost items analyzed were the operational cost, the agricultural amendments and the materials cost. For the crisphead lettuce in monoculture and in intercropping, the COT was R$ 696,37 and R$ 295,06/614,4 m(2) respectively and the productivity was 822.53 and 890.78 kg/614,4 m(2). In monoculture and in intercropping the gross incomes were R$ 489,93 and R$ 452,39/614,4 m(2) respectively. It was verified a loss of R$ 206,44/614,4 m(2) in the crisphead lettuce monoculture and an operational profit of R$ 157,33/614,4 m(2) in protected environment when in intercropping with cucumber.
Economic viability of the crisphead lettuce culture in monoculture and intercropping with cucumber
Keywords: Lactuca sativa; Cucumis sativus; hand labor; Greenhouse; Production cost